2016
DOI: 10.12659/pjr.899315
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging (MRI) Characterization of Perianal Fistulous Disease in a Rural Based Tertiary Hospital of North India

Abstract: SummaryBackgroundTo diagnose and characterize the perianal fistulous disease using Magnetic resonance imaging (MRI) in a hilly and rural area of North India.Material/MethodsThis prospective hospital based study was conducted for a period of one year from April 2014 to April 2015 in the departments of Radiodiagnosis and Surgery of our institute. A total of 50 consecutive patients presenting with perianal fistulous disease fulfilling the inclusion and exclusion criteria were included in the study and taken up fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…Several groups have devised grading systems based on MRI. The St James’ system relates to the fistula anatomy and shows good concordance with surgical findings . Van Assche et al .…”
Section: Imagingmentioning
confidence: 86%
See 1 more Smart Citation
“…Several groups have devised grading systems based on MRI. The St James’ system relates to the fistula anatomy and shows good concordance with surgical findings . Van Assche et al .…”
Section: Imagingmentioning
confidence: 86%
“…Several groups have devised grading systems based on MRI. The St James' system relates to the fistula anatomy [75] and shows good concordance with surgical findings [76]. Van Assche et al [77] have developed a MRI scoring system which includes assessment of the type and number of tracks, the presence and type of extensions, collections and rectal wall thickening and the signal intensity on T2-weighted scans.…”
Section: (Level 1)mentioning
confidence: 99%
“…Few studies have pointed out the false-negative results of the MR imaging 24,27,28 . MR imaging failed to identify two fistulae tracts and two internal openings in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In line with these findings, Singh et al [18] reported high sensitivity of MRI in identification of secondary tract, correct localization of internal opening, and correct detection of horse-shoeing with rates of 93.75%, 95.83%, and 87.5%, respectively. Also, Chauhan et al [19] reported that MRI showed a high sensitivity rate of 93.7% and positive predictive value (PPV) of 96.7% when correlated with surgical findings. Recently, Karanikas et al [20] reported a success rate of 77.4% to demonstrate the presence of a fistula in their series DW-MRI, in comparison to the other pulse sequences, provided high sensitivity and accuracy with 100% specificity for fistula visualization and highest sensitivity, specificity, and accuracy for detection of cavities > 3 mm in diameter.…”
Section: Discussionmentioning
confidence: 99%